The reasons for introducing nano-silica in cementitious layer in pavement - Rezagholilou, Alireza; Nikraz, Hamid (E-Journal of Geotechnical Engineering, 2014)
In pavement, improving soil engineering properties is main purpose of cement application. It is often necessary to increase characteristics of soil cement mixture such as durability, stiffness and strength, whilst reducing moisture sensitivity. In design, achieving to required level of these characteristics may need different cement content that often lead to selection of highest cement content indicated by durability tests. Apart from cost consideration, highest cement content is not necessarily the ideal one by design aspects due to subsequent shrinkage defects. Shrinkage cracking resulted by hydration reactions can cause unpleasant deformations, reduction of bearing capacity and water infiltration. In this paper, some effective and common factors on shrinkage and durability will be reviewed following general discussion on soil cement mixtures. At end, the benefits of nanotechnology product as nano-silica will be introduced in direction of obtaining design objects by optimum cement use. © 2014 ejge.